Adhesives technology for electronic applications : materials, processing, reliability - Licari, James J., 1930- (Materials and processes for electronic applications series., 2011)
This text presents a comprehensive coverage of all aspects of adhesive technology for microelectronic devices and packaging, from theory to bonding to test procedures. In addition to general applications, it includes new developments in anisotropic, electrically conductive, and underfill adhesives.